Isolated gingival overgrowths: A review of case series - Shruti Raizada; Jothi M Varghese; K M Bhat; Kanishk Gupta (Wolters Kluwer Medknow Publications, 2016)
Clinicians are often intrigued by the varied manifestations of the gingival tissue. Gingival overgrowth is a common clinical finding and most of them represent a reactive hyperplasia as a direct result of plaque-related inflammatory gingival disease. These types of growth generally respond to good plaque control, removal of the causative irritants, and conservative tissue management. This case series highlights three different cases of localized gingival overgrowth and its management with emphasis on the importance of patient awareness and motivation.